P2.38 Microbiological analysis from a phase ii study in adults evaluating single doses of gepotidacin (GSK2140944) in the treatment of uncomplicated urogenital gonorrhoea caused by neisseria gonorrhoeae. (8th July 2017) - Scangarella-Oman, N; Hossain, M; Dixon, P; Ingraham, K; Min, S; Tiffany, C; Perry, C; Raychaudhuri, A; Dumont, E; Huang, J; I I I, E Hook; Miller, L
Abstract : Introduction: Gepotidacin (GEP), a novel triazaacenaphthylene antibacterial, inhibits bacterial DNA replication. A Phase 2 study evaluated GEP as a single oral dose (1.5 or 3g) in subjects with urogenital gonorrhoea. Methods: Pre-dose specimens were obtained for culture and susceptibility testing by agar dilution. Microbiological success (MS), was culture confirmed eradication of N. gonorrhoeae (GC) at test-of-cure (TOC), 3–7 days post dose, in the microbiological evaluable (ME) population which consisted of all randomised subjects with culture confirmed urogenital gonorrhoea at baseline, who received any dose of GEP and returned for TOC. Results: Against 69 GC isolates recovered from baseline urogenital specimens in the ME population, GEP minimum inhibitory concentration [MIC (µg/mL)] range was ≤0.06–1 and MIC90 was 0.5. Resistance (R) to comparators were 33%, 28%, 20%, 0%, 0% and 0% for ciprofloxacin (CIP), penicillin, tetracycline, ceftriaxone, cefixime and spectinomycin, respectively. 2 isolates had elevated azithromycin MICs (MICs=2). Overall MS was 96% (66/69) in the ME population. PK/PD analysis showed 100% (61/61) MS when the free area under the curve/MIC ratio ( f AUC/MIC) was ≥48. MS decreased to 63% (5/8) at f AUC/MICs ≤24. All isolates from the 3 urogenital failures were CIP-R, had a baseline GEP MIC=1 and a pre-existing D86N mutation in ParC, a critical residue in GEP binding. 2 were treated with a 3g GEP dose ( f AUC/MICs=24) and 1 was treated with a 1.5g GEP dose ( f AUC/MIC=12). 5 additional isolates with D86N were MS (2 at GEP MIC=1, 3 at GEP MIC ≤0.25). Isolates from 2 failed subjects (3g GEP dose) demonstrated R emergence to GEP (MICs increased ≥32 fold) and had an additional mutation (A92T) in GyrA, also located in GEP binding pocket. Conclusion: Subjects with f AUC/MICs ≥48 were MS, including 3 with D86N ( f AUC/MICs ≥96). Further study of GEP, in the treatment of gonorrhoea is warranted, including demonstration that higher exposures suppress R in key isolate subsets.